Analisis Sistem Informasi Akuntansi Penjualan Yang Ada Di Perum Bulog Divre Bengkulu - Sari, Eka; Wagini, Wagini; Hidayah, Nenden Restu (Journal of Management, Economic, and Accounting, 2022)
the cash sales accounting system is a system carried out by the company by requiring the buyer to pay the price in advance before the goods are handed over by the company to the buyer. cash sales information system includes related functions, documents used, accounting records used, network procedures that make up the system. methods of data collection using field research is to directly review the company by means of observation, interviews and documentation. this type of research uses comparative descriptive, while the analytical method used is a comparative method.the results of the research on cash sales accounting information systems are carried out by comparing cash sales information including related functions, documents used, accounting records used, network procedures that form the system. so from the results of the study it was concluded that the comparison of cash sales accounting information systems when viewed from the purpose of the accounting information system was appropriate/adequate and can be said to be good, this can be seen from the responsibilities of each section that has carried out its duties according to the given authority.